EKSPLORASI MOTIF ANYAMAN TRADISIONAL TEMPAT MAMA SIRIH WARISAN BUDAYA LOKAL DESA TULLENG KECAMATAN LEMBUR KABUPATEN ALOR - Dian Regina Tamara Plaimo; Jellian Padalani; Dermolinda Maipan; Devita T. Mabilehi; Halena Muna Bekata; Dewi S. Maleikari; Dematrius Prabila; Petrus Mau Tellu Dony (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
The purpose of this study was to present the Exploration of Traditional Wicker Motifs of Mama Betel Place as Local Cultural Heritage of Tulleng Village, Lembur District, Alor Regency. The research technique used in this research is descriptive qualitative, interviews with community leaders Mr Imanuel Bailafa and Isak Samau in Tulleng Village, Lembur District, Alor Regency. The results of this study indicate that the people of Tulleng Village have a culture that is still maintained until now, this is indicated by the existence of a woven betel nut mama place as a Local Cultural Heritage of Tulleng Village, Lembur District, Alor Regency, which is usually used in traditional ceremonies, proposing or asking in a marriage. It has its own uniqueness and each of the motifs has a meaning.